The Effect of Resistance Band and Ankle Weight Training Toward Speed of Mawashigeri Jodan Kicks for Semarang Inkai Athletes - Hartono, Ameilia Sawitri; Abdulaziz, Moch Fahmi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The speed of the mawashigeri jodan kick is an important factor for athletes who excel because it can produce high points. This study aims to determine which training method is more effective between training using resistance bands and ankle weights on the speed of the mawashigeri jodan kick in Inkai athletes in Semarang City. The research sample consisted of 30 athletes aged 11-14 years, who were then divided into 2 groups with the A-B-B-A technique, namely the resistance band group and the ankle weight group. This study used a quantitative approach with an experimental method. The research instrument was a measurement of the mawashigeri jodan kick for 30 seconds. The results showed that training with resistance bands provided an average increase of 27.64%, higher than training using ankle weights, which only reached an average of 25.94%.